Re-Scaling stadtregionaler Governance und Planung in Europa: eine Einleitung zum Themenheft - Zimmermann, Karsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
The article gives an introduction to the special issue about recent developments in metropolitan governance in Europe. The special issue seeks to contribute to a comparison of metropolitan governance with a particular emphasis on national policy initiatives. The presentation of recent developments in the six countries Germany, Italy, France, Poland, Spain and England follows a common framework. This framework is built on theories of rescaling and governance. All six countries have experienced dynamic changes in the scale and scope of metropolitan regionalism with different results. The contributions to the special issue show national policy initiatives as well as local case studies of metropolitan governance in terms of their history, structure and recent performance. The chapters show path-dependent developments in Germany, France and Spain as well as path-breaking changes in Poland, Italy and England. All in all, besides the fact that metropolitan regions are still high on the political agenda, a high degree of variation with regard to national policies remains.